The oral cavity is a potential reservoir of gram-negative antimicrobial-resistant bacteria, which are correlated with ageing and the number of teeth - Tomoki Kawayanagi; Miki Kawada-Matsuo; Toru Takeshita; Mi Nguyen-Tra Le; Mikari Asakawa; Yo Sugawara; Chika Arai; Kazuhisa Ouhara; Hiromi Nishi; Noriyoshi Mizuno; Hiroyuki Kawaguchi; Hideki Shiba; et al. (Heliyon)
Objectives: The suppression of antimicrobial-resistant bacteria (ARB) is an important issue worldwide. In recent years, the presence of various ARB in the oral cavity has been reported, but the details remain unclear. Therefore, we aimed to isolate ARB from the oral cavity and investigate the factors affecting ARB colonization. Methods: Third-generation cephalosporin- or carbapenem-resistant gram-negative bacteria (GN-ARB) were isolated from the oral and nasal cavities of 514 participants who visited the dental clinic, and the whole-genome sequences of all the isolates were obtained. Additionally, the tongue microbiota was analysed by 16S rRNA sequencing. The correlations of GN-ARB isolation with clinical status and the tongue microbiota were subsequently investigated. Results: Among 514 participants, 131 and 13 GN-ARB strains were isolated from the oral cavities of 93 participants (18.1 %) and from the nasal cavities of 12 participants (2.3 %). The ARB were mainly affiliated with Acinetobacter spp. (39.7 %), Pseudomonas spp. (14.5 %) and Stenotrophomonas maltophilia (18.3 %). We found a correlation between the isolation of oral GN-ARB and ageing/the number of teeth. There were no significant correlations between the presence of GN-ARB and tongue microbiota composition. Conclusions: Our results suggest that the oral cavity is an important potential reservoir of GN-ARB and that ageing and tooth loss are risk factors for the presence of GN-ARB in the oral cavity.